Analysis of students' generic science skills at Muhammadiyah 22 Surakarta Elementary School. - Desstya, Anatri; Anami, Isnaini (Paedagogia: Jurnal Pendidikan, 2023)
Science learning in elementary schools is expected to provide students with an understanding of scientific terms through experiments that can provide generic science skills. But this is still rarely done at the elementary school level. This study aims to analyze the science generic skills of elementary school students as an effort by the teacher to create learning that is able to make students understand and remember scientific terms. This study is qualitative approach. Sources of data in this study were obtained from class teachers and fifth grade students at Elementary School Muhammadiyah 22 Surakarta. Data collection techniques using observation, interviews and documentation. Test the validity of the data using the credibility test and source triangulation. Data analysis techniques consist of data collection, data presentation, drawing conclusions, and verification. The results showed that students' generic science skills in science learning obtained a percentage of 75%. The highest score is in the aspect of symbolic language (25%) shown by the activities of students mentioning symbols, symbols and scientific terms in presentations related to the water cycle process. The lowest score 0% absence of student activities. The research contribution is teachers must teach science through experimental activities of measuring rainfall, or similar experiments that are adapted to the topic of the material so that aspects of generic science skills can be developed in a more balanced way in each aspect so as to be able to provide more comprehensive science skills and knowledge in learners.